Improving fibre utilisation and protein supply in animals fed poor quality roughages: ILRI nutrition research and plans - Osuji, P.O.; Fernández Rivera, S.; Odenyo, A.A. (International Livestock Research Institute, 1995)
Inadequate nutrition is the main cause of low productivity of livestock in sub-Saharan Africa. The primary feed resources include fodder trees, natural pastures and crop residues. This paper presents results from studies conducted at ILRI in evaluations of these resources. The effect of supplementing teff straw with lablab or cowpea in cattle on microbial protein supply was evaluated using urinary purine derivatives. There was no effect of type of supplement but the level of supplementation significantly improved microbial protein supply. Similarly, supplementing maize stover with oilseed cake increased total microbial protein flow in sheep. Teff straw supplemented with Sesbania sesban increased dry matter degradation and liquid passage rates. Degradation of Sesbania, Leucaena, Chamaecytisus and Vernonia foliage was also evaluated. Sesbania was degraded rapidly and Vernonia slowly. The effects of anti-nutrient extracts from Vernonia amygdalina, Chamaecytisus palmensis, Sesbania sesban and Acacia angustissima were tested on pure cultures of cellulolytic rumen microbes and A. angustissima prolonged the lag phase. A angustissima killed sheep and Tephrosia caused massive rumen statis. Studies conducted in semi-arid West Africa indicated that the microbial digestive activity, as measured by the disappearance in sacco of a standard forage, varies both seasonally and across animal species. Genetic variation in feeding value of crop residues, forage legumes and fodder trees were assessed. The variation among varieties of sorghum and pearl millet were relatively small and inconsistent across years. Relatively larger differences were observed in forage legumes. Preliminary results suggest possibilities for identifying geographical areas that produce better quality fodder trees. Future work should include the biochemical basis of the interactions between rumen microbes and the chemicals contained in fodder trees, and the seasonal variations of microbial populations in various ruminants across agro-ecological zones.